Predictors of Mortality, Drug Resistance, and Determinants among Carbapenem-Resistant Enterobacterales Infections in Chinese Elderly Patients - Yufei Zhang; Chengyun Zou; Jie Qin; Muyi Li; Xing Wang; Tian Wei; Haiying Wang (Canadian Journal of Infectious Diseases and Medical Microbiology)
Elderly patients with carbapenem-resistant Enterobacterales (CRE) infections represent considerable mortality rates. But data on the risk factors for the death of elderly patients following such infection remain limited. We aimed to assess the clinical outcomes, identify mortality-associated risk factors, and determine the antibiotic resistance and resistance genes of isolates for these patients. Hospitalized patients aged ≥65 years with CRE infection from January 2020 to December 2020 were retrospectively reviewed. Isolates identification and molecular characterization of CRE were carried out. Logistic regression analysis was applied to assess the potential factors associated with mortality. Of the 123 elderly patients with CRE infection included in our study, the all-cause mortality rate was 39.8% (49/123). The most prevalent pathogen was carbapenem-resistant Klebsiella pneumoniae (CRKP, 116 of 123). The overall rates of multidrug-resistant (MDR) and extensively drug-resistant (XDR) were 100.0% and 66.7%. All CRE isolates exclusively harbored a singular variant of carbapenemase gene, such as blaKPC−2, blaIMP−4, blaNDM−5, or blaOXA−48, while 98.4% of isolates harbored more than one β-lactamase gene, of which 106 (86.2%) isolates harbored blaCTX−M, 121 (98.4%) isolates harbored blaTEM, and 116 (94.3%) isolates harbored blaSHV. Multivariable logistic regression analysis revealed that mechanical ventilation (adjusted odds ratio (AOR) = 33.607, 95% confidence interval (CI): 4.176-270.463, P<0.001), use of tigecycline during hospitalization (AOR = 5.868, 95% CI: 1.318-26.130, P=0.020), and APACHE II score (AOR = 1.305, 95% CI: 1.161–1.468, P<0.001) were independent factors associated with increasing the mortality of patients with CRE infection, while admission to intensive care unit (ICU) during hospitalization (AOR = 0.046, 95% CI: 0.004–0.496, P=0.011) was a protective factor. CRE-infected elderly patients with mechanical ventilation, use of tigecycline during hospitalization, and high APACHE II score were related to poor outcomes. The isolates carried various antibiotic genes and presented high antibiotic resistance. These findings provide crucial guidance for clinicians to devise appropriate strategies for treatment.